CYBER TRAVELING AND CINEMATIC REALITY: Experiences of the K-Drama Fans - Safira, Btari Anya; Badaruddin, Muhammad (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2021)
Involvement in globalization and enjoying various different cultures become easier. With new development in the entertainment industry, K-drama consumers from every corner of the world able to experience Korean daily life and its atmosphere that is delivered into their gadgets. Our research shows that the quality of experience gained by our source from the new entertainment product is relatively similar to the experiences they gained from traveling in general. This phenomenon revealed the new traveling experience which is called cyber traveling, while consumers who enjoy k-drama in our research become our model of cyber traveler. Besides that, the success of the cyber traveling experience is in the presence of cinematic reality. Our research finding shows several facts about what kind of experiences that traveler received through the cinematic reality of k-drama. The finding is also telling about experiences that are similar to daily life, or other experience when a traveler could not distinguish between k-drama visualization and real daily life. Our research use phenomenology as the main method, while in-depth interview, observation, documentation, and online document searching as data collecting methods. This research revealed that the cyber traveling experience could change our sources’ perception about the comparison between real traveling and cyber traveling. In conclusion, we could also see that cyber traveling has become an alternative or in further development even a substitute for real traveling. To cite this article (7th APA style):Safira, B. A. & Badaruddin, M. (2021). Cyber traveling and cinematic reality: Experiences of the k-drama fans. Journal Communication Spectrum: Capturing New Perspectives in Communication, 11(2), 108-118. http://dx.doi.org/10.36782/jcs.v11i1.2150